International humanitarian law and military intervention: reflections on operation allied forces in the former federal republic of Yugoslavia in 1999 - Sixpence, Pedzisai; Chilunjika, Alouis (International Journal of Law and Public Policy, 2022)
Military intervention is a crucial tool used to compel nation states to abide by the principles of international law. The United Nations, through its Charter (Chapter VII) authorises the use of force by the UN and or regional organisations as a legitimate scheme of settling international disputes. A closer look on the majority of these interventions, however, shows that the conduct of the forces taking part in these interventions turn to violate some crucial principles of international law. Additional Protocol 1 of 1977 to the 1949 Geneva protocols provides for the regulations in terms of the conduct of forces in an armed conflict to minimise civilian carnage and injuries as well as damage on civilian objects. This paper assessed the effectiveness of International Humanitarian Law (IHL) in cases of a military intervention. The study was a case study focusing on the experiences of the North Atlantic Treaty Organisation (NATO) forces that intervened in the former Federal Republic of Yugoslavia (FRY) in 1999. The study depended on secondary sources of information. The paper reveals that forces taking part in these operations normally harm civilian population and objects beyond reasonable proportion if they do not pay attention to the details on the ground. The paper then recommends that more should be done to uphold and adhere to the provisions of Chapter VI of the UN Charter while ensuring that forces taking part in military interventions are parties to key international legislations that govern their conduct to prevent states from purposefully violate the law.